Put the steps in order that are used to solve the following systems of equations by substitution. −7x−2y=−13

x−2y=11 don't give me steps in words just put the numbers in order

x - 2y = 11 --> x = 2y + 11
-16y = 64
-16y - 77 = -13
x - 2(-4) = 11
x + 8 = 11
y = -4
x = 3
-14y - 77 -2y = -13
-7 (2y + 11) -2y = -13
(3, -4)

1 answer

-14y - 77 - 2y = -13
-7(2y + 11) - 2y = -13
-16y - 77 = -13
-16y = 64
y = -4
x - 2(-4) = 11
x + 8 = 11
x = 3

The steps in order to solve the system of equations by substitution are:
1. Rewrite one of the equations in terms of one variable.
2. Substitute the expression from step 1 into the other equation.
3. Solve the resulting equation for the variable.
4. Substitute the value of the variable from step 3 into one of the original equations to find the value of the other variable.
5. The solution is the values of the variables found in step 3 and step 4, represented as an ordered pair. In this case, the solution is (3, -4).